Decoding the functional roles of intronic microRNA miR-2355 and its host gene KLF7 in immunobiology of cervical cancer - Samia, Nure Sharaf Nower (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2021.